Synthesis and characterization of Gd2O2S:Pr3+ nanophosphors using gamma irradiation method - Muhammad Hassyakirin Hasim,; Irman Abdul Rahman,; Sapizah Rahim,; Muhammad Taqiyuddin Mawardi Ayob,; Liyana Mohd Ali Napia,; Shahidan Radiman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Praseodymium ion, Pr3+ doped Gd2O2S nanophosphors were successfully synthesized via gamma irradiation route along with the heat treatment. The effect of the gamma irradiation (0-150 kGy) on the structural, morphology and photoluminescence properties of Gd2O2S:Pr3+ were characterized via X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and photoluminescence spectroscopy (PL). The thermal properties of precursor sample were tested by the thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The chemical bonding of the precursor samples were analyzed by Fourier transform infrared spectroscopy (FT-IR). The XRD result confirmed the formation of hexagonal phase of Gd2O2S:Pr3+ without the presence of any impurities. The FESEM inspection showed the non-symmetrical shape of particles transformed into grain-like shape. The optimum photoluminescence (PL) emission intensities of Gd2-xO2S:xPr3+ occur at 50 kGy dose of gamma irradiation and 2 mol% concentration dopant of Pr3+ ions. The spectra under 325 nm UV excitation shows a strong green emission at 515 nm, which match the 3P0 → 3H4 transition of Pr3+ ions. The Gd2O2S:Pr3+ nanophosphors possessed many useful approaches in various applications mainly as radiation detection and biomedical diagnostic.